A Novel Virtual Coaching System Based on Personalized Clinical Pathways for Rehabilitation of Older Adults-Requirements and Implementation Plan of the vCare Project - Sofoklis Kyriazakos; Hannes Schlieter; Kai Gand; Massimo Caprino; Massimo Corbo; Peppino Tropea; Elda Judica; Irma Sterpi; Stefan Busnatu; Patrick Philipp; Jordi Rovira; Alvaro Martínez; et al. (Frontiers Media S.A., 2020)
Home-based rehabilitation after an acute episode or following an exacerbation of a chronic disease is often problematic with a clear lack of continuity of care between hospital and home care. Secondary prevention is an essential element of long-term rehabilitation where strategies oriented toward risk reduction, treatment adherence, and optimization of quality of life need to be applied. Frail and sometimes isolated, the patient fails to adhere to the proposed post-discharge clinical pathway due to lack of appropriate clinical, emotional, and informational support. Providing a suitable rehabilitation after an acute episode or a chronic disease is a major issue, as it helps people to live independently and enhance their quality of life. However, as the rehabilitation period usually lasts some months, the continuity of care is often interrupted in the transition from hospital to home. Virtual coaches could help these patients to engage in a personalized rehabilitation program that complies with age-related conditions. These coaches could be a key technology for empowering patients toward increasing their adherence to the care plan and to improve their secondary prevention measures. In this paper, we are presenting a novel virtual coaching system that will address these challenges by combining recent technological advances with clinical pathways, based on joint research and validation activities from researchers from the medical and information and communication technology (ICT) domains.